2020
DOI: 10.1161/jaha.119.015709
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Conduction Disorders as Markers of Cardiac Events in Myotonic Dystrophy Type 1

Abstract: Background Myotonic dystrophy type 1 involves cardiac conduction disorders. Cardiac conduction disease can cause fatal arrhythmias or sudden death in patients with myotonic dystrophy type 1. Methods and Results This study enrolled 506 patients with myotonic dystrophy type 1 (aged ≥15 years; >50 cytosine‐thymine‐guanine repeats) and was treated in 9 Japanese hospitals for neuromuscular diseases from January 2006 to August 2016. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…However, less than 3% of patients received ICDs, which is very low compared with other countries (PM 10.1% and ICD 3.4% 25 ; PM + ICD 14% 26 ; PM 21% and ICD 1% 27 ). A Japanese study similarly showed that only 3.3% of DM patients used implantable devices 28 . Thus, our data confirm that implantable devices are not widely used for DM in Japan.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, less than 3% of patients received ICDs, which is very low compared with other countries (PM 10.1% and ICD 3.4% 25 ; PM + ICD 14% 26 ; PM 21% and ICD 1% 27 ). A Japanese study similarly showed that only 3.3% of DM patients used implantable devices 28 . Thus, our data confirm that implantable devices are not widely used for DM in Japan.…”
Section: Discussionsupporting
confidence: 78%
“…A Japanese study similarly showed that only 3.3% of DM patients used implantable devices. 28 Thus, our data confirm that implantable devices are not widely used for DM in Japan.…”
Section: Parotid Tumor 15supporting
confidence: 71%
“…Cardiac involvement is a prominent feature of DM1 and is the second leading cause of mortality in affected individuals, following respiratory insufficiency due to skeletal muscle wasting ( 16 , 17 ). In various population studies in patients with adult-onset DM1, cardiac manifestations have been noted in patient groups with a median age of 40 years ( 18 , 19 ). Recent reports have also described cardiac disease features in children with congenital DM1 ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the cause of sudden death is unclear, and sudden death also occurs in patients with no antecedent history of cardiac issues. Various large-scale studies have reported correlations between the presence of conduction defects, pacemaker implantation, age, size of the CTG repeat expansion, atrial arrhythmias, family history and male sex and the risk of sudden death [ 27 , 28 , 29 , 51 , 52 , 53 ]. In contrast, other studies have reported no correlations between CTG repeat size and sudden death [ 54 ].…”
Section: Ecg and Conduction Defects In Dm1mentioning
confidence: 99%